First, let’s try to isolate the variable, x. One of the x terms is inside the parentheses on the left. So, let’s start by getting rid of the parentheses to make this equation easier to work with. One way to do this is to distribute the 2 to the x and to the 3. You can think of this as (2·x)+(2·3). Rewrite the left side.

2(x+3) = 3x+4
? + ? = 3x+4

1 answer

To distribute the 2 to both terms inside the parentheses on the left side of the equation \( 2(x + 3) = 3x + 4 \), we can perform the following steps:

  1. Distribute 2 to \( x \): \( 2 \cdot x = 2x \)
  2. Distribute 2 to \( 3 \): \( 2 \cdot 3 = 6 \)

Now, we can rewrite the left side of the equation as follows:

\[ 2x + 6 = 3x + 4 \]

So, the equation becomes:

\[ 2x + 6 = 3x + 4 \]

This shows the left side rewritten as \( 2x + 6 \) and is equal to \( 3x + 4 \) on the right side.